Labor analgesia with ropivacaine added to clonidine: a randomized clinical trial - Nakamura, Giane (2008)
CONTEXT AND OBJECTIVE: Previous studies have led to speculation that the association between ropivacaine and clonidine might be more effective than ropivacaine alone. We examined the maternal-fetal effects of two pharmacological approaches: a low dose of ropivacaine or a lower dose of ropivacaine plus clonidine for epidural analgesia during labor. DESIGN AND SETTING: Prospective study at Department of Anesthesiology, Faculdade de Medicina de Botucatu, Universidade Estadual Paulista. METHODS: Thirty-two pregnant women in American Society of Anesthesiologists physical status I and II randomly underwent epidural analgesia using 15 ml of ropivacaine 0.125% (R group) or 15 ml of ropivacaine 0.0625% plus 75 µg clonidine (RC group). Pain intensity, sensory block level, latency time, motor block intensity, duration of labor analgesia and duration of epidural analgesia were evaluated. The newborns were evaluated using Apgar scores and the Amiel-Tison method (neurological and adaptive capacity score). RESULTS: There were no statistically signifi cant differences between the groups regarding pain score, sensory block level, duration of epidural analgesia or Apgar score. The latency time, duration of labor analgesia and motor block were R group < RC group. The half-hour and twohour neurological and adaptive capacity scores were higher in the R group. All of the R group newborns and 75% of the RC group newborns were found to be neurologically healthy at the 24-hour examination. CONCLUSION: Both low-dose ropivacaine and a lower dose plus clonidine relieved maternal pain during obstetric labor. Newborns of mothers who received only ropivacaine showed better neurological and adaptive capacity scores.